The effect of 3-bromopyruvate on human colorectal cancer cells is dependent on glucose concentration but not hexokinase II expression. Issue 1 (19th February 2016) - Ho, Nelson; Morrison, Jodi; Silva, Andreza; Coomber, Brenda L.
Abstract : Colorectal cancer cells respond to 3BP via phosphorylation of AKT at residue Thr-308. The availability of glucose in culturing media plays a crucial role in 3BP sensitivity, although independently of HKII expression. Abstract : Cancer cells heavily rely on the glycolytic pathway regardless of oxygen tension. Hexokinase II (HKII) catalyses the first irreversible step of glycolysis and is often overexpressed in cancer cells. 3-Bromopyruvate (3BP) has been shown to primarily target HKII, and is a promising anti-cancer compound capable of altering critical metabolic pathways in cancer cells. Abnormal vasculature within tumours leads to heterogeneous microenvironments, including glucose availability, which may affect drug sensitivity. The aim of the present study was to elucidate the mechanisms by which 3BP acts on colorectal cancer (CRC) cells with focus on the HKII/Akt signalling axis. High HKII-expressing cell lines were more sensitive to 3BP than low HKII-expressing cells. 3BP-induced rapid Akt phosphorylation at site Thr-308 and cell death via both apoptotic and necrotic mechanisms. Cells grown under lower glucose concentrations showed greater resistance towards 3BP. Cells with HKII knockdown showed no changes in 3BP sensitivity, suggesting the effects of 3BP are independent of HKII expression. These results emphasize the importance of the tumour microenvironment and glucose availability when considering therapeutic approaches involving metabolic modulation.